Isolation and characterization of porcine monoclonal antibodies revealed two distinct serotype-independent epitopes on VP2 of foot-and-mouth disease virus. (19th July 2021) - Li, Kun; Zhu, Guoqiang; Zhou, Shasha; Sun, Pu; Wang, Hengmei; Bao, Huifang; Fu, Yuanfang; Li, Pinghua; Bai, Xingwen; Ma, Xueqing; Zhang, Jing; Li, Dong; et al.
Abstract : Pigs are susceptible to foot-and-mouth disease virus (FMDV), and the humoral immune response plays an essential role in protection against FMDV infection. However, little information is available about FMDV-specific mAbs derived from single B cells of pigs. This study aimed to determine the antigenic features of FMDV that are recognized by antibodies from pigs. Therefore, a panel of pig-derived mAbs against FMDV were developed using fluorescence-based single B cell antibody technology. Western blotting revealed that three of the antibodies (1C6, P2-7E and P2-8G) recognized conserved antigen epitopes on capsid protein VP2, and exhibited broad reactivity against both FMDV serotypes A and O. An alanine-substitution scanning assay and sequence conservation analysis elucidated that these porcine mAbs recognized two conserved epitopes on VP2: a linear epitope ( 2 KKTEETTLL 10 ) in the N terminus and a conformational epitope involving residues K63, H65, L66, F67, D68 and L81 on two β-sheets (B-sheet and C-sheet) that depended on the integrity of VP2. Random parings of heavy and light chains of the IgGs confirmed that the heavy chain is predominantly involved in binding to antigen. The light chain of porcine IgG contributes to the binding affinity toward an antigen and may function as a support platform for antibody stability. In summary, this study is the first to reveal the conserved antigenic profile of FMDV recognized by porcine B cells and provides a novel method for analysing the antibody response against FMDV in its natural hosts (i.e. pigs) at the clonal level.